Precedents of Intention to Adopt Big Data Management for Higher Education Institutions in Malaysia - Rosmaini TASMIN; Tan Lay HUEY; Ramatu Muhammad NDA; Ishaq JAAFAR (Communications of International Proceedings, 2021)
Big data is one prime mover in this Industrial Revolution 4.0 era. Many industrial and service firms have actively charted their ways and directions towards incorporating and implementing big data approach into their strategic planning and daily business operations too. However, observing into this new phenomenon one could observe that public institutions, such as universities, are rather slacken in embracing what this new technology and approach could bring and benefit their bottom lines. Hence, higher education institutions (HEIs) must also apply big data to further efficiently engage information technology tools to empower academic effectiveness and performance. This study looks at the features of big data that are relevant to educational institutions, as well as the factors that influence the implementation of big data in higher education institutions, especially for strategic management purposes. It also looks at the problems of implementing big data in HEIs. This research employs a qualitative analysis approach to interview and analyze evidences from few public and private university academicians, in order to meet all of the stated objectives. This study is expected to establish the most significant precedents, emphasizing the role of big data management in delivering HEIs with improved educational outcomes and guiding students, schools, and universities towards enhanced experience and performance. Technology Awareness, Technology Readiness, Technology Reliability, Top Management Support, and Technology Infrastructure are five factors that influence the decision to implement big data management (BDM) in such institutions. The findings evince that the top management support and technology readiness are the two major precedents that strongly pushing forward the BDM initiative to get adopted among the surveyed organizations. The graphical evidence on deducing this conclusion could be derived from the analysis of coded texts and radar charts from the interviewing sessions.
Keywords: Big Data; Higher Education Institution; Adoption; Factors; Challenges.